MENINGKATKAN KETERAMPILAN DASAR MENGAJAR KIMIA MELAUI PEMBELAJARAN BERBASIS BOARD GAME (BGBL) - Habiddin Habiddin (FKIP USK, 2013)
The Course of Basic skills of teaching is provided to train chemistry education students in conducting an efficient and effective learning. These skills include set induction closure lesson skills and explaining skills. In the next globalization of education era, chemistry education students as the future chemistry teachers are expected to have a good skill in teaching in English. In fact, the limitations of their abilities and self-confidence to speak in English cause they did not apply the basic skills of teaching in English properly, especially when they have to explain chemistry concepts with analogies and told the interesting stories related to chemistry. To solve this problem, the design of learning to optimize student opportunities in practicing their speaking skills is the right solution. This learning design is called Board Game-Based Learning (BGBL). BGBL implementation is effective in improving students’ confidences in demonstrating their set induction closure lesson skills and explaining skills in teaching chemistry in English.